2016
DOI: 10.1016/s0140-6736(16)31405-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of China's universal two-child policy

Abstract: In October, 2015, China’s one-child policy was replaced by a universal two-child policy. The effects of the new policy are inevitably speculative, but predictions can be made based on recent trends. The population increase will be relatively small, peaking at 1·45 billion in 2029 (compared with a peak of 1·4 billion in 2023 if the one-child policy continued). The new policy will allow almost all Chinese people to have their preferred number of children. The benefits of the new policy include: a large reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
459
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(473 citation statements)
references
References 55 publications
12
459
0
2
Order By: Relevance
“…The results presented here combined the data of nearly 37 original studies and provided significant evidence for clinical practice, seeking to promote the need to include an orthodontic focus in public dental services. The statistical analysis showed that approximately 47.92% of Chinese schoolchildren presented with one or several types of anomalies, which were comparable to the neighbouring country of Japan at 46.5% . Moreover, variations were observed in the prevalence rates across different genders, malocclusion types, geographical regions, years, and provinces.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The results presented here combined the data of nearly 37 original studies and provided significant evidence for clinical practice, seeking to promote the need to include an orthodontic focus in public dental services. The statistical analysis showed that approximately 47.92% of Chinese schoolchildren presented with one or several types of anomalies, which were comparable to the neighbouring country of Japan at 46.5% . Moreover, variations were observed in the prevalence rates across different genders, malocclusion types, geographical regions, years, and provinces.…”
Section: Discussionmentioning
confidence: 79%
“…According to the latest report by the National Bureau of Statistics of China, the size of the Chinese population increased by 9.68% between 2000 and 2017 to 1.39 billion people, and there are 23.353 million children under the age of fourteen. Furthermore, with the universal implementation of the two‐child policy in mainland China in October 2015, the number of Chinese children has continued to increase in recent years, which may increase the demand for health services, especially child health services . Epidemiological studies have also indicated that the prevalence of malocclusion in the Chinese population ranges from 14.9% to 93.5% .…”
Section: Introductionmentioning
confidence: 99%
“…That report estimated the global EOD incidence rate as 0.41 (95% CI 0.36–0.47) cases/1,000 live births and the LOD incidence rate as 0.26 (95% CI 0.21–0.30) cases/1,000 live births. The number of cases and birth cohort was one third more during the prospective than retrospective period, possibly because China implemented a 2-child policy in October 2015 ( 17 ). The incidence of invasive GBS was similar between the prospective and retrospective periods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to some influential reports such as Zeng and Hesketh (2016), universal two-child policy is predicted to have a relatively small effect on population and economic growth. We understand the increasing uncertainty due to the two-child policy in China; however, the population scenario is a large research project which is not suitable to discuss intensively in this paper.…”
Section: Assumptions Of Explanatory Variables Out Of Samplementioning
confidence: 99%